New paradigms in sustainable energy systems with hydrogen - Dincer, Ibrahim; Aydin, Muhammed Iberia (PERGAMON-ELSEVIER SCIENCE LTD, 2023)
Climate change, disturbance of the energy security resulting from increasing fuel prices due to conflicts, and disruptions to production and supply chains caused by COVID-19 have highlighted the need for the world to be prepared for future challenges. The environmental and climate change impacts of heavy use of fossil fuels for energy production have yielded numerous crucial challenges and will even cause increasingly more severe effects in the years to come. This is particularly important, as the utilization of fossil fuels is the largest contributor to the increasing emissions of greenhouse gases in the atmosphere, which is leading to climate change and other problems. As a result, there is an emerging need to transition towards low or zero-emission energy systems where renewables and nuclear energy can play a critical role in the new energy equation and help establish the source ecosystem for hydrogen. Hydrogen, being the most abundant, clean, and energy-intensive element in nature, is an attractive alternative to fossil fuels. Furthermore, when produced using renewable energy sources, it is easier to reduce and control upstream emissions to produce or store hydrogen than fossil fuels. This study presents a framework for developing hydrogen technologies, building the necessary infrastructure, and selecting appro-priate energy sources to help transition to a more sustainable and resilient energy system. There are also life cycle assessment studies conducted for various energy production technologies, including hydrogen, and their results are comparatively evaluated to confirm renewables and nuclear energy options would be the most suitable sources for hydrogen production. The global warming potential values of electricity production using nuclear and renewable energy are found to be 0.027 and 0.043 kg CO2 eq./kWh. Comparatively, the global warming po-tential for natural gas, oil and coal are found to be 0.2, 0.3 and 0.36 kg CO2 eq./kWh, respectively.
Keywords: Hydrogen; Nuclear energy; Renewables; Fossil fuels; Climate change; Energy management; Sustainability; TECHNOLOGIES; INNOVATION; OPTIONS; Thermodynamics; Energy & Fuels; Mechanics